2015
DOI: 10.1038/srep18385
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanoparticle-mediated hyperthermia stimulates dispersal in bacterial biofilms and enhances antibiotic efficacy

Abstract: The dispersal phase that completes the biofilm lifecycle is of particular interest for its potential to remove recalcitrant, antimicrobial tolerant biofilm infections. Here we found that temperature is a cue for biofilm dispersal and a rise by 5 °C or more can induce the detachment of Pseudomonas aeruginosa biofilms. Temperature upshifts were found to decrease biofilm biomass and increase the number of viable freely suspended cells. The dispersal response appeared to involve the secondary messenger cyclic di-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 62 publications
0
79
0
1
Order By: Relevance
“…40 At higher concentrations, CHX attacks the bacterial cytoplasmic membrane and denatures microbial proteins. CHX has both a rapid onset of bactericidal action and prolonged antimicrobial efficacy through residual effects.…”
mentioning
confidence: 99%
“…40 At higher concentrations, CHX attacks the bacterial cytoplasmic membrane and denatures microbial proteins. CHX has both a rapid onset of bactericidal action and prolonged antimicrobial efficacy through residual effects.…”
mentioning
confidence: 99%
“…In 2016, Situ et al improved the material properties of SPIONs and demonstrated that Zn-doping can enhance performance and antibiofilm efficacy in E. coli biofilms (Situ et al, 2016). Similarly, magnetic hyperthermia coupled with antibiotics has been shown to eradicate biofilms formed by S. epidermidis (Geilich, Gelfat, Sridhar, van de Ven, & Webster, 2017) and P. aeruginosa (Nguyen, Duong, Selvanayagam, Boyer, & Barraud, 2015). These studies demonstrate the versatility of magnetic nanoparticle (MNP)-mediated hyperthermia for the disruption of different types of biofilms.…”
Section: Beyond the Traditional Antibiotic Drug Treatment And Reimpmentioning
confidence: 99%
“…A further development is silicon NPs with polymer-like strands holding an anti-cancer drug; these degrade upon entering the cells and discharge the contents (48). Research also aims to develop NPs to target bacteria including gold NPs irradiated with infrared light and iron oxide (FeO) NPs coated with polymer (49).…”
Section: Nanotechnologymentioning
confidence: 99%